Manajemen Perpustakaan Sekolah dalam Meningkatkan Minat Baca Peserta Didik - Miranti Andella; Miftahul Husni; Ermita; Fifin Wildanah (CV. ITTC INDONESIA, 2025)
The school library holds a crucial role in fostering students’ reading interest. Effective and innovative library management is essential in creating an environment that encourages reading habits. This study aims to explore various school library management strategies that can enhance students’ interest in reading. The research employs a literature review method by examining relevant sources such as academic journals, books, and research reports. Findings indicate that successful management strategies include providing engaging and relevant reading materials, arranging the library space to be comfortable and inspiring, integrating information technology into library services, and implementing creative literacy programs that actively involve students. Moreover, collaboration among librarians, teachers, and parents is vital in cultivating a reading culture within the school community. With the application of optimal library management strategies, students’ reading interest can significantly increase, ultimately contributing to the overall quality of education.